Decision Support Framework for Water Management to Enhance Resource Use Efficiency - Garg, Kaushal K.; Singh, Ramesh; Anantha, K.H.; Venkataradha, A. (International Crops Research Institute for the Semi-Arid Tropics, 2025)
Effective water management in rainfed and semi-arid regions demands a shift toward evidence-based planning to enhance resource use efficiency. To address this, a decision support framework was developed that integrates Land Resource Inventory (LRI) data with hydrological assessments. By systematically quantifying water availability, sectoral demands, and supply-demand gaps, the framework utilizes detailed water budgeting to evaluate specific requirements for agriculture, domestic use, and livestock. These analytics serve to guide Natural Resource Management (NRM) and cropping system planning. Implementation across benchmarking clusters in Maharashtra, India, demonstrated that aligning interventions with local biophysical realities stabilizes groundwater levels and optimizes investment prioritization. Ultimately, this approach enables a transition from reactive interventions to proactive, sustainable development